Molecular Diversity of Endophytic Fungi Isolated from Different Sections of Local Fruit Trees - Sim, Jiun Horng (2010)
Over the past three decades, endophytic fungi have attracted increasing attention among taxonomists, agronomists, ecologists and evolutionary scientist. Endophytic fungi are fungi species that live within a plant for at least part of its life without causing apparent disease. Virtually every plant studied to date harbors at least one species of endophytic fungi. It now appears that an enormous, relatively untapped source of microbial diversity is represented by endophytic fungi. Scientific literature had highlighted that the tropical plants of the world are the main source of these microbial endophytes. Malaysia as an agriculture based country; the rich soil allows for many fruits to grow in abundance and throughout the year. Fruit has become one of the major export items that contribute millions income to our country. Since tropical fruit plays an important role as food and as an economic commodity, there is a need to clearly understand the microorganisms that co-exist within the fruit. In order to study the potential endophytic fungi that exhibit in our local fruits, 27 common local fruits have been chosen for this study. The results indicated that all of the targeted local fruits harbor at least one endophytic fungal. Different media are believed to be amenable for the isolation of different endophyties. Therefore, three types of media namely PDA, SCA and ACT were included in this study. Potato Dextrose Agar (PDA) showed the highest recovery rate (39%) as compared to Starch Casein Agar (SC) (37%) and Actinomycetes Agar (ACT) (24%). After a series of isolation and purification processes, DNA of the isolated fungi was extracted using the conventional sodium dodecyl sulphate (SDS) method. In order to characterize the isolated fungi sample, molecular techniques based on the internal transcribe sequence (ITS) and random amplified polymorphic DNA (RAPD) were applied. Ribosomal DNA (rDNA) is the most conserved region in the genome, with capabilities of phygenetic divergence. The ITS region is now perhaps the most widely sequenced DNA region in fungi. It is typically the most useful tool for molecular systematic at the species level, and even within species. All isolated endophytic fungal DNA samples were subject to ITS primer set (ITS-1 and ITS-4) screening and all of the samples of DNA were able to generate distinct banding after the polymerase chain reaction. Obtained bands were further subjected to direct sequencing to gain relative coding nucleotide sequence. The gene sequences obtained were aligned using NCBI Blast search and analyzed by the use of bioinformatics software BioEdit and Bionumericsver 5.0. The results revealed that the endophytic fungi isolates were attributed to 23 different genera and all of the its region sequence of endophytic fungal isolates. The accession numbers of all the sequences were generated from GenBank database. In order to study the phylogenetic relationship between the isolates, an analysis based on the comparison of neighbor neighbouring sequences of ITS region were performed. Results of the analysis have showed that all the local isolates share a high percentage of similarity in their ITS region sequences and tend to cluster together as compared to the available sequences from the genome. RAPD is an amplification based technique that use arbitrary primer to detect the changes in the DNA sequence which enable the discrimination of the samples according to their comparative DNA sequences. A total of 20 different arbitrary primers were screened in the RAPD analysis, and only three arbitrary primers (OPO 6, OPO10 and OPO16) that gave reproducible and discriminatory banding pattern were selected. Results exhibited comparable high level of genetic diversity based on the isolated endophytic fungi which come from the same source. Besides, result in this study also revealed that composite analysis of all three selected primers provide better discrimination ability to distinguish between unrelated strains. A bimolecular characterization was performed after the identification of the isolates using well diffusion antimicrobial assay against 14 bacterial cultures. A total of 53 isolates displayed antimicrobial activity against at least one tested microorganism. Among all the isolates, sample 62 which was identified as Botrysphaeria sp. Gave the most significant inhibiting results against growth of all tested microorganisms. Conclusion, research based on endophyte-local fruit interactions has strengthened and pooled understanding of diversity, basic biology and ecology of the endophytic fungi combined with tropic interactions and multi-species co-evaluation. It also leads to novel ways to discover endophytic fungi’s role in the ecosystem especially in fruit. While more comprehensive understanding of microbial communities has theoretical interest, it provides valuable knowledge of causes and consequences of microbial mediated interactions in terrestrial ecosystems which may have economical value when developing sustainable management strategies for forestry, and restoring damaged terrestrial ecosystems.